L-Cell Expression of Melanocortin-4-Receptor Is Marginal in Most of the Small Intestine in Mice and Humans and Direct Stimulation of Small Intestinal Melanocortin-4-Receptors in Mice and Rats Does Not Affect GLP-1 Secretion - Kuhre, Rune E.; Modvig, Ida M.; Jepsen, Sara L.; Kizilkaya, Hüsün S.; Bæch-Laursen, Cecilie; Smith, Christopher A.; Reimann, Frank; Gribble, Fiona M.; Rosenkilde, Mette M.; Holst, Jens J. (Frontiers in Endocrinology, 2021)
The molecular sensors underlying nutrient-stimulated GLP-1 secretion are currently being investigated. Peripheral administration of melanocortin-4 receptor (MC4R) agonists have been reported to increase GLP-1 plasma concentrations in mice and humans but it is unknown whether this effect results from a direct effect on the GLP-1 secreting L-cells in the intestine, from other effects in the intestine or from extra-intestinal effects. We investigated L-cell expression of MC4R in mouse and human L-cells by reanalyzing publicly available RNA sequencing databases (mouse and human) and by RT-qPCR (mouse), and assessed whether administration of MC4R agonists to a physiologically relevant gut model, isolated perfused mouse and rat small intestine, would stimulate GLP-1 secretion or potentiate glucose-stimulated secretion. L-cell MC4R expression was low in mouse duodenum and hardly detectable in the ileum and MC4R expression was hardly detectable in human L-cells. In isolated perfused mouse and rat intestine, neither intra-luminal nor intra-arterial administration of NDP-alpha-MSH, a potent MC4R agonist, had any effect on GLP-1 secretion (P ≥0.98, n = 5–6) from the upper or lower-half of the small intestine in mice or in the lower half in rats. Furthermore, HS014—an often used MC4R antagonist, which we found to be a partial agonist—did not affect the glucose-induced GLP-1 response in the rat, P = 0.62, n = 6). Studies on transfected COS7-cells confirmed bioactivity of the used compounds and that concentrations employed were well within in the effective range. Our combined data therefore suggest that MC4R-activated GLP-1 secretion in rodents either exclusively occurs in the colon or involves extra-intestinal signaling.